Androgen-associated and androgen-independent causes of alopecia and acne in women. Literature review - І. В. Сідорова; Т. М. Тутченко; О. А. Бурка; Л. М. Семенюк; I. Г. Ноговська; Л. В. Дем’яненко (Reproduktivnaâ èndokrinologiâ, 2020)
This article refers to the issues of alopecia and acne pathogenesis: anatomy of hair and sebaceous glands, biological factors affecting the stages of hair development and function of sebaceous glands. Alopecia is divided into two large groups: scaring and non-scaring alopecia, the later is represented by alopecia areata, telogen effluvium, and female pattern hair loss/androgenetic alopecia (FPHL/AGA). Before starting the search for systemic causes it is necessary to predetermine the type of alopecia on the basis of medical history and external manifestations. FPHL /AGA as a most common form of alopecia can often coexist with another common pathology – telogen effluvium, this fact determines therapeutic approaches and their results.Main pathogenetic mechanisms, approaches to differential diagnostics and treatment of the main specified types of non-scarring alopecia are reviewed. FPHL/AGA is a main type of alopecia which is often referred to gynecologists/endocrinologists. It is now regarded a multifactorial pathology with the involvement of a genetic component, androgen receptor gene expression, dihydrotestosterone synthesis and local low grade inflammation specifics. FPHL/AGA can be with and without hyperandrogenism, in both cases it can be accompanied by an increased risk of metabolic syndrome. In case of FPHL/AGA with hyperandrogenism the success of treatment depends on the consistent coordinated work of gynecologist/endocrinologist and dermatologist/trichologist, which allows combining systemic and local therapy in a timely manner.Also contemporary views on the acne pathogenesis are reviewed. Given the complex nature of acne its therapy is also complex and stepwise. According to current clinical guidelines and recent studies of the microbial component of acne pathogenesis the following conclusions are formulated. Patients with acne require assessment of androgen status, determination of the hyperandrogenism source, including evaluation of tissue androgens; phenotype of the syndrome and cardio-metabolic risks should be determined in patients with polycystic ovary syndrome; it is advisable to determine antimicrobial susceptibility of pathogens isolated from the inflamed pilosebaceous unit if acne form requires the local or systemic antibacterial therapy. В статье раскрыты вопросы, важные для понимания патогенеза алопеции и акне – анатомия волос и сальных желез, биологические факторы, влияющие на фазы развития волос и функцию сальных желез. Алопеция делится на две большие группы: рубцовая и нерубцовая алопеция, которая представлена гнездовой алопецией, телогеновым выпадением волос (ТВВ) и потерей волос по женскому типу/андрогенетической алопецией (ПВЖТ/АГА). Перед началом поиска системных причин необходимо предварительное определение разновидности алопеции на основе данных анамнеза и внешних проявлений. Кроме того, наиболее распространенная форма алопеции, ПВЖТ/АГА, в определенные периоды времени может сочетаться с другой распространенной патологией – телогеновым выпадением волос; этот факт определяет терапевтические подходы и их результаты.Рассмотрены основные патогенетические механизмы, подходы к дифференциальной диагностике и лечению основных указанных видов нерубцовой алопеции. Разновидность алопеции, с которой часто приходится сталкиваться гинекологам/эндокринологам, а именно ПВЖТ/АГА, сегодня рассматривается как мультифакторная патология с привлечением генетического компонента, особенностями экспрессии гена андрогенового рецептора и синтеза дигидротестостерона, особенностями течения локальных воспалительных процессов в ткани скальпа. ПВЖТ/АГА может иметь место на фоне гиперандрогении и без нее, при этом в обоих случаях сопровождается повышенным риском метаболического синдрома. В случае ПВЖТ/АГА с гиперандрогенией успешность лечения зависит от последовательной скоординированной работы гинеколога/эндокринолога и дерматолога/трихолога, что позволяет сочетать и вовремя корректировать системную и местную терапию.В статье также рассмотрены современные взгляды на патогенез акне. Учитывая комплексную природу акне, их терапия тоже является комплексной и поэтапной. Согласно действующим клиническим рекомендациям и данным недавних исследований микробной составляющей патогенеза акне, сформулированы следующие выводы: пациентки с акне требуют оценки андрогенного статуса, определения источника гиперандрогении, включая оценку тканевых андрогенов; у пациенток с синдромом поликистозных яичников должна определяться фенотипическая форма синдрома и проводиться оценка кардиометаболических рисков; при формах акне, которые подлежат лечению с применением местной или системной антибактериальной терапии, целесообразно определение антибиотикочувствительности патогена, выделенного из воспаленной пилосебационной единицы. У статті розкриті питання, важливі для розуміння патогенезу алопеції й акне – анатомія волосся та сальних залоз, біологічні фактори, що впливають на фази розвитку волосся та функцію сальних залоз. Алопеція поділяється на дві великі групи: рубцева та нерубцева алопеція, яка представлена гніздовою алопецією, телогеновим випадінням волосся і втратою волосся за жіночим типом/андрогенетичною алопецією (ВВЖТ/АГА). Перед початком пошуку системних причин необхідне попереднє визначення різновиду алопеції на основі даних анамнезу і зовнішніх проявів. Також найрозповсюдженіша форма алопеції, ВВЖТ/АГА, у певні періоди часу може поєднуватися з іншою розповсюдженою патологією – телогеновим випадінням волосся; цей факт визначає терапевтичні підходи та їх результати. Розглянуто основні патогенетичні механізми, підходи до диференційної діагностики та лікування основних зазначених видів нерубцевої алопеції. Різновид алопеції, з якою найчастіше доводиться стикатись гінекологам/ендокринологам, а саме ВВЖТ/АГА, сьогодні розглядається як мультифакторна патологія із залученням генетичного компоненту, особливостями експресії гену андрогенового рецептора та синтезу дигідротестостерону, особливостями перебігу локальних запальних процесів в тканині скальпа. ВВЖТ/АГА може мати місце на фоні гіперандрогенії та без неї, при цьому в обох випадках супроводжується підвищеним ризиком метаболічного синдрому. В разі ВВЖТ/АГА з гіперандрогенією успішність лікування залежить від послідовної скоординованої роботи гінеколога/ендокринолога і дерматолога/трихолога, що дозволяє поєднувати і вчасно коректувати системну і місцеву терапію. У статті також розглянуті сучасні погляди на патогенез акне. Зважаючи на комплексну природу акне, його терапія теж є комплексною і поетапною. Згідно з чинними клінічними рекомендаціями і даними нещодавніх досліджень мікробної складової патогенезу акне, сформульовані наступні висновки: пацієнтки з акне потребують оцінки андрогенного статусу, визначення джерела гіперандрогенії, включаючи оцінку тканинних андрогенів; у пацієнток із синдромом полікістозних яєчників має визначатись фенотипова форма синдрому і проводитись оцінка кардіометаболічних ризиків; при формах акне, які лікують із застосуванням місцевої або системної антибактеріальної терапії, доцільним є визначення антибіотикочутливості патогену, виділеного із запаленої пілосебаційної одиниці.